2010
DOI: 10.1179/174328810x12647087218992
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of interferential therapy on clinical and experimentally induced pain

Abstract: Background: Interferential therapy (IFT) is one of the most popular modalities used by physiotherapists for the management and control of pain. Despite its widespread use, there remains debate surrounding its effectiveness.Objectives: The aim of this systematic review was to evaluate the published literature on the effectiveness of IFT in reducing pain. Method: A literature search of Cochrane Central Register of Controlled Trials, Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulative In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…4 Interferential therapy (IFT) has been reported to be one of the most common electrotherapeutic modalities used by physiotherapists worldwide. 5 The concept of IFT is based on crossing two medium frequency currents (with a carrier frequency between 2 and 10 KHz, most commonly 4 KHz) that reportedly generates a low-frequency 'beating'(amplitude-modulated) effect between 0 and 150 Hz in the deep tissues. 6,7 These beat frequencies are believed to decrease pain in the region of the application and assist with the reduction of oedema and improvement of joint range of motion (ROM) depending on the selected frequency.…”
Section: Introductionmentioning
confidence: 99%
“…4 Interferential therapy (IFT) has been reported to be one of the most common electrotherapeutic modalities used by physiotherapists worldwide. 5 The concept of IFT is based on crossing two medium frequency currents (with a carrier frequency between 2 and 10 KHz, most commonly 4 KHz) that reportedly generates a low-frequency 'beating'(amplitude-modulated) effect between 0 and 150 Hz in the deep tissues. 6,7 These beat frequencies are believed to decrease pain in the region of the application and assist with the reduction of oedema and improvement of joint range of motion (ROM) depending on the selected frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This review reported a limitation in the number of studies that incorporated IFC as a single treatment, while stating that IFC might be effective if used in addition to other treatment interventions. The second review investigated the analgesic effect of IFC on either the clinical or induced pain [26]. According to the authors of the second review, the evidence of IFC effectiveness in pain management isinadequate, and included only nine randomized trials, eight of which were conducted on artificially-induced pain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been an increasing number of studies addressing IFC as an experimental or control treatment for painful musculoskeletal conditions [26,27]. The results of these studies might help to improve the quality of evidence, provide a better understanding of the role of IFC in relieving musculoskeletal pain, and identifying the best parameters that could achieve this effect [28].…”
Section: Introductionmentioning
confidence: 99%
“…Interferential therapy (IFT) is a highly popular treatment modality in the clinical setting, which involves crossing two medium frequency currents to generate a low-frequency beating effect in the deep tissues [22], and can be used alone or combined with massage [23]. Although IFT is purported to provide pain relief and increased blood flow to the tissues [24], there is still inadequate evidence to support its use as a sole intervention for pain management in musculoskeletal disorders in general [22], and in shoulder pain in particular [25,26]. Nevertheless, IFT as a supplement to other interventions has demonstrated advantages over placebo and control treatments for reducing musculoskeletal pain [27], although there are conflicting findings on this issue [28].…”
Section: Introductionmentioning
confidence: 99%